Avaliação da possível participação do polipeptídeo intestinal vasoativo e substância P na patologia do megaesôfago induzido pela infecção pelo trypanosoma cruzi - Rodolfo Duarte Nascimento (2013)
The chagasic megaesophagus is one of the major clinical changes in digestive form of Chagas disease. Among the main characteristics of this condition, we can mention enlargement of the esophagus wall, loss of peristalsis and difficulty in swallowing food. The inflammatory process is considered as an important factor responsible for injuries in the Enteric Nervous System. These lesions started in the acute phase of the infection, and it may persist into the chronic phase, which can lead the development of mega. Studies have shown that changes in the profile of neuropeptides, such as vasoactive intestinal polypeptide (VIP) and substance P are capable of promoting changes in epithelial barrier, motor disorders and induce inflammation in several diseases affecting the gastrointestinal tract (GI). This study aimed to look for evidences of VIP and substance P involvements in the pathology of Trypanosoma cruzi-induced megaesophagus. It was demonstrated immunoreactivity to VIP and substance P in nerve fibers, eosinophils and epithelial cells of the esophagus in individuals infected with and without megaesophagus and in uninfected individuals. Furthermore, it was shown epithelial cells, blood vessels, and mononuclear cells immunostained with VPAC2 and NK1, the receptors for VIP and substance P, respectively. Besides, VPAC2 immunoreactivity was also observed on polymorphonuclear cells, smooth muscle cells and enteroglial cells, in all groups examined. The semi-quantitative analyzes revealed decreased in the relative density of VIP-IR nerve fibers and increased in the relative density of substance P-IR fibers, in patients with megaesophagus; increase in the percentage of eosinophils VIP-IR and substance P-IR and decrease in the density epithelial cells immunostained with VIP, substance P-IR, VPAC2-IR and NK1-IR. It was further demonstrated that, in individuals infected without megaesophagus, there are positive correlations between inervation and the relative density of VIP-IR nerve fibers, and also between the percentages of eosinophils immunostaing for VIP and substance P and the number of neurons. Given these data we dare suggest that changes in the profile of VIP and substance P should contribute to the pathology of chagasic megaesophagus, through its interference in inflammation and homeostasis of the mucosal epithelial barrier.